Low-Temperature Synthesis of ZnO Nanoparticles Using a Water-Methanol Solvent for Rhodamine B Photodegradation - Christanti, Cindy Claudia; Benu, Didi Prasetyo (Jurnal Beta Kimia, 2025)
Water pollution caused by organic dyes represents a significant environmental issue demanding effective treatment methods. This study aimed to synthesize zinc oxide (ZnO) nanoparticles at a low temperature using a water-methanol mixed solvent and evaluate their photocatalytic potential for the degradation of Rhodamine B (RhB). ZnO nanoparticles were successfully synthesized at a low temperature of 60°C utilizing a mixture of water and methanol as the solvent. Characterization results from X-ray diffraction (XRD) and Field Emission Scanning Electron Microscopy (FESEM) confirmed that the synthesized material consists of wurtzite structure ZnO nanoparticles. Analysis using UV-Vis Diffuse Reflectance Spectroscopy (DRS) showed that the material possesses a band gap energy of 3.16 eV. The as-synthesized ZnO nanoparticles exhibited effective photocatalytic activity for the degradation of the model pollutant RhB under UV light irradiation. A high photodegradation efficiency of 95.58% was achieved within 45 minutes, with a first-order reaction rate constant (k) of 0.0571 min⁻¹. This low-temperature synthesis method based on the water-methanol solvent mixture proved to be a promising and efficient route for producing active ZnO photocatalysts potentially applicable in treating organic dye-contaminated wastewater.